Setting rents in residential real estate: a methodological proposal using multiple criteria decision analysis - Canas, Sílvia R. D.; Ferreira , Fernando A. F.; Meidutė-Kavaliauskienė, Ieva (International Journal of Strategic Property Management, 2015)
The real estate sector has been negatively affected by the recent economic recession, which has forced structural changes that impact property value and price. Recent pressures have also motivated reduced liquidity and access to credit, causing a drop in property sales and, thus, boosting the rental housing market. It is worth noting, however, that the rental housing segment is not with-out difficulties and complexity, namely in terms of legislation and rental value revaluation. In light of this reasoning, this study aims to develop a multiple criteria decision support system for calculation of residential rents. By integrating cognitive maps and the measuring attractiveness by a categorical based evaluation technique (MACBETH), we also aim to introduce simplicity and transparency in the decision making framework. The practical implications, advantages and shortfalls of our proposal are also analyzed.First Publish Online: 23 Dec 2015